ERROR ANALYSIS IN SOLVING MATHEMATICAL LITERACY PROBLEMS ON THE MATERIAL OF ARITHMETIC SEQUENCES AND SERIES - Syahadat, Prasasti Bumi; Kamaliyah, Kamaliyah; Sari, Asdini (Jurnal Pendidikan Matematika dan IPA, 2025)
Mathematical literacy equips students with the skills to solve real-life problems effectively. However, many students struggle to understand and apply mathematical concepts effectively. This study aims to analyze the types of errors made by 35 students of the X2 class of SMA Negeri 9 Banjarmasin in solving mathematical literacy problems on the material of arithmetic sequences and series based on Newman's procedure. This procedure was chosen because it provides a structured framework that identifies specific stages where learners commonly make mistakes in solving mathematical problems, such as reading, comprehension, transformation, process skills, and encoding. Data were collected through written tests and interviews, then analyzed using a descriptive qualitative method based on the Miles and Huberman technique. The results showed that encoding errors (27.48%) were the most frequent, where students often skipped verification and struggled to draw accurate conclusions. Process skills errors (26.06%) occurred when students were confused about the next step despite knowing the correct formula. Transformation errors (21.81%) stemmed from incorrect application of formulas due to reliance on memorization without contextual understanding. Comprehension errors (21.53%) resulted from misunderstanding the problem, especially in identifying known and unknown information. Reading errors (3.12%), the least frequent, are typically caused by unfamiliarity with mathematical terms or symbols. These findings indicate that students"™ difficulties are both procedural and conceptual. Therefore, instructional strategies should emphasize concept mastery, promote strategic problem-solving, encourage self- verification, and connect mathematics to real-world situations.